The Anthem companion to Philip Rieff - Imber, Jonathan B. (Book Network Int'l Limited trading as NBN International (NBNi) : Anthem Press, 2018)
The Anthem Companion to Phillip Rieff' offers the best contemporary work on Phillip Rieff, written by the best scholars currently working in this field. Original, authoritative and wide-ranging, the critical assessments of this volume will make it ideal for Rieff students and scholars alike. 'Anthem Companions to Sociology' offer authoritative and comprehensive assessments of major figures in the development of sociology from the last two centuries. Covering the major advancements in sociological thought, these companions offer critical evaluations of key figures in the American and European sociological tradition, and will provide students and scholars with both an in-depth assessment of the makers of sociology and chart their relevance to modern society.